The Role of Psychoeducation in Preventing Stunting: Tackling Early Marriage Culture in Adolescent - Kusuma Wardani, Novita Eka; Harumi, Ani Media; Sholika, Siti Mar’atus (Journal La Medihealtico, 2025)
Stunting is a chronic nutritional issue threatening future generations, significantly influenced by early marriage practices. In East Java, Indonesia, early marriage has become a pressing concern, with a 10.44% increase in 2022, exceeding the national average. The region reported the highest number of early marriage dispensation requests in Indonesia, totaling 15,337 cases, or 29.4% of the national total. In the Madurese community, early marriage is often viewed as a customary practice, driven by unintended pregnancies and parental pressure. This study aims to evaluate the effectiveness of psychoeducation regarding stunting and early marriage culture in promoting stunting prevention behaviors among adolescent girls. A mixed-method approach was employed, using a quasi-experimental design with pre- and post-test groups, focusing on female adolescents aged 14-21 at the Wonoayu community health center. The independent variables include psychoeducation on stunting and early marriage culture, while the dependent variable is stunting prevention behavior. Data were collected using questionnaires for the quantitative aspect and in-depth interviews for the qualitative component. Results indicate significant improvements in stunting prevention behavior scores post-intervention. Psychoeducation effectively enhances knowledge about stunting's causes and preventive measures, enabling adolescents to take proactive steps. Furthermore, it fosters positive attitudes toward nutrition and reproductive health, encouraging healthier habits among participants.